Bilateral Sudden Sensorineural Hearing Loss and Intralabyrinthine Hemorrhage in a Patient With COVID-19. Issue 1 (January 2021) - Chern, Alexander; Famuyide, Akinrinola O.; Moonis, Gul; Lalwani, Anil K.
Abstract : Objective: To describe a case of bilateral sudden sensorineural hearing loss (SSNHL) and intralabyrinthine hemorrhage in a patient with COVID-19. Study Design: Clinical capsule report. Setting: Tertiary academic referral center. Patient: An adult woman with bilateral SSNHL, aural fullness, and vertigo with documented SARS-CoV-2 infection (IgG serology testing). Interventions: High-dose oral prednisone with taper, intratympanic dexamethasone. Main Outcome Measures: Audiometric testing, MRI of the internal auditory canal with and without contrast. Results: A patient presented with bilateral SSNHL, bilateral aural fullness, and vertigo. Serology testing performed several weeks after onset of symptoms was positive for IgG COVID-19 antibodies. MRI showed bilateral intralabyrinthine hemorrhage (left worse than right) and no tumor. The patient was treated with two courses of high-dose oral prednisone with taper and a left intratympanic dexamethasone injection, resulting in near-resolution of vestibular symptoms, a fluctuating sensorineural hearing loss in the right ear, and a severe to profound mixed hearing loss in the left ear. Conclusions: COVID-19 may have otologic manifestations including sudden SSNHL, aural fullness, vertigo, and intralabyrinthine hemorrhage.